Congestion in the bathtub. Issue 4 (December 2015) - Fosgerau, Mogens
Abstract: This paper presents a model of urban traffic congestion that allows for hypercongestion. Hypercongestion has fundamental importance for the costs of congestion and the effect of policies such as road pricing, transit provision and traffic management, treated in the paper. In the simplest version of the model, the unregulated Nash equilibrium is also the social optimum among a wide range of potential outcomes and any reasonable road pricing scheme will be welfare decreasing. Large welfare gains can be achieved through road pricing when there is hypercongestion and travelers are heterogeneous. Abstract : Highlights: A dynamic model of urban congestion in the style of Vickrey (1969). Based on macroscopic fundamental diagram. Allows for hypercongestion. Allows transit mode, elastic demand, and various sorts of heterogeneity.